2001
DOI: 10.1152/ajpheart.2001.281.1.h404
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning attenuates apoptosis and necrosis: role of protein kinase Cε and -δ isoforms

Abstract: Preconditioning reduces cardiomyocyte necrosis in vivo and in vitro, but it is unknown whether preconditioning blocks apoptosis. We wanted to compare the effects of preconditioning on necrosis and apoptosis in cardiomyocytes. Necrosis was detected with propidium iodide, and apoptosis was quantified by three complementary techniques: flow cytometry, TdT-mediated dUTP nick-end labeling assay, and DNA-laddering electrophoresis. Apoptosis increased with simulated ischemia time (6 h, 19 +/- 1%; 12 h, 27 +/- 2%; 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 34 publications
1
35
0
1
Order By: Relevance
“…Moreover, the latest data suggest that PKC-␦ can be a proapoptotic molecule by functioning as a lamin kinase, disassembling lamina during apoptosis. That PKC-⑀ can be protective, whereas PKC-␦ can be destructive, is also suggested by other studies (27,39). Very few studies have been carried out examining the role of PKC during cold storage, and in one, the use of nonspecific PKC inhibitors has been shown to improve rat heart preservation (16).…”
Section: Calcium Calpain Calpastatin and Pkc In Cold Ischemia-repementioning
confidence: 78%
“…Moreover, the latest data suggest that PKC-␦ can be a proapoptotic molecule by functioning as a lamin kinase, disassembling lamina during apoptosis. That PKC-⑀ can be protective, whereas PKC-␦ can be destructive, is also suggested by other studies (27,39). Very few studies have been carried out examining the role of PKC during cold storage, and in one, the use of nonspecific PKC inhibitors has been shown to improve rat heart preservation (16).…”
Section: Calcium Calpain Calpastatin and Pkc In Cold Ischemia-repementioning
confidence: 78%
“…brane translocations of nPKC and NMDA receptors in mouse hippocampal slices (Liu et al, 2001;Fanjun et al, 2006). It is proposed that morphine-induced nitrogen oxide release mediates neuroprotection in a human neuroblastoma cell line against intracellular oxidative stress and neuroinflammation (Rambhia et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies with isolated heart models have shown that A 1 -AR overexpression increases myocardial resistance to ischemia by constitutively activating endogenous signaling pathways, with mitochondrial K ATP channels being critical effectors (14,21). Because A 1 -AR-mediated cardiac protection shares at least some common mechanisms with ischemic preconditioning (17,21), it is logical that other signaling intermediates [such as protein kinase C (16,18) and tyrosine kinase] are also held in common. Recently, p38 mitogen-activated protein kinase was found to be an important signaling component in the cardioprotection induced by preconditioning and adenosine (4,7,20).…”
Section: Discussionmentioning
confidence: 99%